CSR Communication on Social Media : A Comparative Analysis of Global and Local Beauty Brands - Neustroeva, Sandaara (2025)
This thesis explores how beauty brands communicate Corporate Social Responsibility on social media and how consumers perceive and respond to these messages. It compares three global brands, L’Oréal Paris, Estée Lauder, and L’Occitane, with two Czech brands, Manufaktura and Havlíkova Apotéka, across Instagram, Facebook, and YouTube, examining what they post about CSR, how often they post it, and how audiences engage. The study combines a content analysis of social media posts with an online consumer survey to identify common themes, preferred formats, perceived authenticity, and links to intended behaviors such as willingness to purchase or recommend. The findings highlight where brand communication aligns with what consumers notice and trust, and suggest practical directions for more effective CSR messaging.